Early Childhood Teachers' Perceptions of the Importance of Understanding Neuroscience - Shinta Aprilia; Nelly Marhayati; Bakhrul Ulum (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to explore early childhood education (ECE) teachers’ perceptions regarding the importance of understanding neuroscience. The study employs a qualitative descriptive approach using a survey method. Data were collected through Google Forms questionnaires distributed via WhatsApp to 20 ECE teachers in Bengkulu City. The findings show that most teachers understand the basic concept of neuroscience and the importance of stimulating early brain development. A total of 15 teachers demonstrated adequate understanding of neuroscience in early childhood education, while a smaller number still lack sufficient understanding. These results indicate the need to enhance teachers’ knowledge of neuroscience through continuous professional development.